Vitamin D levels in epileptic children on long-term anticonvulsant therapy - Fathy Pohan; Aryono Hendarto; Irawan Mangunatmadja; Hartono Gunardi (Paediatrica Indonesiana, 2015)
Background Long-term anticonvulsant therapy, especially with enzyme inducers, has been associated with low 25-hydroxyvitamin D [25(OH)D] levels and high prevalence of vitamin D deficiency. However, there have been inconsistent results in studies on the effect of long-term, non-enzyme inducer anticonvulsant use on vitamin D levels.Objective To compare 25(OH)D levels in epileptic children on long-term anticonvulsant therapy and non-epileptic children. We also assessed for factors potentially associated with vitamin D deficiency/insufficiency in epileptic children.Methods This cross-sectional study was conducted at two pediatric neurology outpatient clinics in Jakarta, from March to June 2013. Subjects in the case group were epileptic children, aged 6-11 years who had used valproic acid, carbamazepine, phenobarbital, phenytoin, or oxcarbazepine, as a single or combination therapy, for at least 1 year. Control subjects were non-epileptic, had not consumed anticonvulsants, and were matched for age and gender to the case group. All subjectsâ€™ 25(OH)D levels were measured by enzyme immunoassay.Results There were 31 epileptic children and 31 non-epileptic control children. Their mean age was 9.1 (SD 1.8) years. Most subjects in the case group were treated with valproic acid (25/31), administered as a monotherapy (21/31). The mean duration of anticonvulsant consumption was 41.9 (SD 20) months. The mean 25(OH)D level of the epileptic group was 41.1 (SD 16) ng/mL, lower than the control group with a mean difference of 9.7 (95%CI 1.6 to 17.9) ng/mL. No vitamin D deficiency was found in this study. The prevalence of vitamin D insufficiency in the epileptic group was higher than in the control group (12/31 vs. 4/31; P=0.020). No identified risk factors were associated with low 25(OH)D levels in epileptic children.Conclusion Vitamin D levels in epileptic children with long-term anticonvulsant therapy are lower than that of non-epilepticÂ children, but none had vitamin D deficiency.